(untitled) (Experimental biology, 2019)
The article describes the distribution, structural features and comparative analysis of coenopopulations of an endemic rare Altai plant species Amygdalus ledebouriana Schlecht. As a result of this study, the territories of its distribution in Eastern Kazakhstan have been studied. Populations were marked on the territory of the Naryn and Kalibinsky ranges in the shrub belt. The studies were carried out by the route reconnaissance method from 2016 to 2018. Based on this study, the authors identified four populations of A. ledebouriana Schlecht. on the ridge Naryn. Two populations were found in the shrub belt of this ridge, in the northeastern shrub slope of the Sary-Shoky mountain near the village of Kokterek (N: 49º05’, E: 84º29’; N: 49º08’, E: 84º49’). The third population was located in the southwestern foothills of the Bukhtarma mountains in the vicinity of Ylken Naryn Нарын (N: 49º08’, E: 84º49’). The fourth one was found on the southeastern foothills of the Narym Range, near the village of Cherdoyak (N: 48º48’, E: ISSN 1563-0218; eISSN 2617-7498 Experimental Biology. №1 (78). 2019 37 83º55’), in the valley of the river Zheneshke. The article provides data on the specific growing conditions of A. ledebouriana populations on the Naryn ridge. Key words: Amygdalus ledebouriana Schlecht., species, rare, endemic, coenopopulation, population, habitat.